An Evaluation by the Class Teachers Instructing the Religious Culture and Ethics Course in Primary Schools of the Teaching and Learning Process - Süreyya Ürgün; Sevim Güven (Uluslararası Türk Eğitim Bilimleri Dergisi)
Values instilled in students during the primary school years have a lasting impact on their lives. Among the values that should be taught are religion and ethics, imparted first by families. However, they are taught through the Religious Culture and Ethics (RCE) course during the school years. In the formal educational institutions of our country, RCE education starts in the fourth-grade class of primary school. At schools without subject teachers, the RCE course, scheduled as two hours per week in primary schools, is delivered by class teachers. Based on this situation, the research sought to determine the class teachers' evaluations of the RCE course they teach in primary schools. The research was designed using a phenomenological approach. The research's study group consisted of 30 participants determined by criterion sampling among class teachers working at state schools in Ağrı province and instructing the RCE course in the 2022-2023 academic year. The data were obtained through the structured face-to-face interview, one of the qualitative data collection methods, and analyzed through content analysis. According to the research findings, the participants concurred that the teachers teaching the RCE course should possess pedagogical content and basic religious knowledge. Another finding was that it is essential to use applications and technology to make the RCE course more efficient. It was also found that fourth-grade students struggle to comprehend some abstract religious concepts as they are in the concrete operational period. Moreover, the textbook is insufficient and needs to be simplified in content and language. Consequently, it was discovered that the class teachers instructing this course encountered a number of challenges, yet they had recommendations for enhancing the teaching process.